QoS in video conferencing applications - Mishev, Anastas; Filiposka, Sonja (Firenze University Press, 2012)
In recent years there has been a tremendous increase in the capacity of networks and an accompanying increase in the consumption of that capacity. Some applications, such as interactive multimedia applications, not only require large amounts of bandwidth, but also require specialized services from the network with respect to latency and loss. The network must accommodate such traffic without unduly degrading the performance of other applications in the network, some of which may be mission critical. IP videoconferencing is one such application that requires special services from the network. This paper describes the possibilities of providing network Quality of Service (QoS) to videoconferencing applications.